Gender awareness in Wotawati in the 15th century - Aristiono Nugroho (Interdisciplinary Social Studies, 2025)
This research investigates gender awareness in Wotawati, Pudung Village, Girisubo District, through the historical narrative of Raden Joyo Sukmo and his wife, Nyai Arum Sukmawati, in the 15th century. The study aims to understand their relationship as a model of mutual respect and cooperation, contributing to social cohesion in the community. Employing a qualitative approach, data were collected through interviews with 12 informants and secondary sources from local government documents. The findings reveal that Raden Joyo Sukmo exemplified gender awareness by valuing his wife's contributions, fostering an environment of shared decision-making, and promoting equality in household duties. Their partnership not only highlighted the significance of gender dynamics but also served as a catalyst for community development and cultural preservation. The implications of this research underscore the importance of historical narratives in understanding contemporary gender issues and encourage inclusive participation in gender discussions. Future research should explore the impact of gender awareness on community development across various cultural contexts and examine other historical figures that exemplify similar dynamics to enhance current gender equality initiatives.